An accurate algorithm of numerical integration for computing seismic responses of inelastic structures - Ijima, K; Miyahara, M; Obiya, H; Zakaria, Muhammad Nizam (International Journal of Integrated Engineering, 2018)
The paper proposes an algorithm that makes numerical integrations with conditions for stability to be usable for computing inelastic seismic responses of structures. The numerical integrations with conditions cannot be applied to solving directly the equation of the motion, but the numerical integrations utilized for linear problems generally give exacter responses than that without any conditions. The method of modal analysis can clear the condition by applying the eigenvalue analysis to the equation of the motion expressed by the tangent stiffness in the inelasticity. The paper shows considerable difference between the result by the numerical integration with conditions and that without any condition, and the former result will be exacter than the latter from several proofs in the discussion